An ocean practices maturity model: from good to best practices - Carlo Mantovani; Jay Pearlman; Anna Rubio; Rachel Przeslawski; Mark Bushnell; Pauline Simpson; Lorenzo Corgnati; Enrique Alvarez; Simone Cosoli; Hugh Roarty (Frontiers in Marine Science, 2024)
Ocean practices, intended as a wide spectrum of methodologies supporting ocean-related research, operations, and applications, are constantly developed and improved to enable informed decision-making. Practices start from the idea of an individual or a group and often evolve towards what can be called good or best practices. This bottom-up approach may in principle result in different paths for the evolution of each practice, and ultimately generate situations where it is not clear to a new user how to compare two practices aiming at the same objective, and determine which one is best. Also, although a best practice is supposed to be the result of a multi-institutional collaborative effort based on the principles of evidence, repeatability and comparability, a set of individual requirements is not yet defined in literature for a practice to be considered a good, better, and ultimately a best practice. This paper proposes a method for addressing those questions and presents a new maturity model for ocean practices, built upon existing maturity models for systems and software, developed and adopted in the last decades. The model provides attributes for assessing both the maturity of the practice description and its implementation. It also provides a framework for analyzing gaps and suggesting actions for practice evolution. The model has been tested against a series of widely adopted practices and the results are reported and discussed. This work facilitates a common approach for developing and assessing practices, from which greater interoperability and trust can be achieved.

Multi-Platform, High-Resolution Study of a Complex Coastal System: The TOSCA Experiment in the Gulf of Trieste - Stefano Querin; Simone Cosoli; Riccardo Gerin; Célia Laurent; Vlado Malačič; Neva Pristov; Pierre-Marie Poulain (Journal of Marine Science and Engineering, 2021)
Although small in size, the Gulf of Trieste (GoT), a marginal coastal basin in the northern Adriatic Sea, is characterized by very complex dynamics and strong variability of its oceanographic conditions. In April–May 2012, a persistent, large-scale anticyclonic eddy was observed in the GoT. This event was captured by both High Frequency Radar (HFR) and Lagrangian drifter observations collected within the European MED TOSCA (Tracking Oil Spill and Coastal Awareness) project. The complexity of the system and the variety of forcing factors constitute major challenges from a numerical modeling perspective when it comes to simulating the observed features. In this study, we implemented a high-resolution hydrodynamic model in an attempt to reproduce and analyze the observed basin-wide eddy structure and determine its drivers. We adopted the Massachusetts Institute of Technology General Circulation Model (MITgcm), tailored for the GoT, nested into a large-scale simulation of the Adriatic Sea and driven by a tidal model, measured river freshwater discharge data and surface atmospheric forcing. Numerical results were qualitatively and quantitatively evaluated against HFR surface current maps, Lagrangian drifter trajectories and thermohaline data, showing good skills in reproducing the general circulation, but failing in accurately tracking the drifters. Model sensitivity to different forcing factors (wind, river and tides) was also assessed.

Depth-Dependent Correction for Wind-Driven Drift Current in Particle Tracking Applications - Mirjam van der Mheen; Charitha Pattiaratchi; Simone Cosoli; Moritz Wandres (Frontiers in Marine Science, 2020)

Best Practices on High Frequency Radar Deployment and Operation for Ocean Current Measurement - Carlo Mantovani; Lorenzo Corgnati; Jochen Horstmann; Anna Rubio; Emma Reyes; Céline Quentin; Simone Cosoli; Jose Luis Asensio; Julien Mader; Annalisa Griffa (Frontiers in Marine Science, 2020)

High-Frequency Radar Observations of Surface Circulation Features along the South-Western Australian Coast - Simone Cosoli; Charitha Pattiaratchi; Yasha Hetzel (Journal of Marine Science and Engineering, 2020)
A new merged high-frequency radar (HFR) data set collected using SeaSonde and WERA (WEllen RAdar) systems was used to examine the ocean surface circulation at diurnal, seasonal and inter-annual time scales along the south-west coast of Australia (SWWA), between 29°–32° S. Merging was performed after resampling WERA data on the coarser SeaSonde HFR grid and averaging data from the two HFR systems in the area of common overlap. Direct comparisons between WERA and SeaSonde vectors in their overlapping areas provided scalar and vector correlation values in the range Ru = [0.24, 0.76]; Rv = [0.39, 0.83]; ρ = [0.44, 0.75], with mean bias between velocity components in the range [−0.02, 0.28] ms−1, [−0.16, 0.16] ms−1 for the U, V components, respectively. The lower agreement between vectors was obtained in general at the boundaries of the HFR domains, where the combined effects of the bearing errors, geometrical constraints, and the limited angular field of view were predominant. The combined data set allowed for a novel characterization of the dominant features in the region, such as the warmer poleward-flowing Leeuwin Current (LC), the colder Capes Current (CC) and its northward extensions, the presence of sub-mesoscale to mesoscale eddies and their generation and aggregation areas, along with the extent offshore of the inertial-diurnal signal. The contribution of tides was weak within the entire HFR domain (

Implementation of the Listen-Before-Talk Mode for SeaSonde High-Frequency Ocean Radars - Simone Cosoli (Journal of Marine Science and Engineering, 2020)
The International Telecommunication Union (ITU) Resolution 612, in combination with Report ITU-R M2.234 (11/2011) and Recommendation ITU-R M.1874-1 (02/2013), regulates the use of the radiolocation services between 3 and 50 MHz to support high frequency oceanographic radar (HFR) operations. The operational frame for HFR systems include: band sharing capabilities, such as synchronization of the signal modulation; pulse shaping and multiple levels of filtering, to reduce out-of-band interferences; low radiated power; directional transmission antenna, to reduce emission over land. Resolution 612 also aims at reducing the use of spectral bands, either through the application of existing band-sharing capabilities, the reduction of the spectral leakage to neighboring frequency bands, or the development and implementation of listen-before-talk (LBT) capabilities. While the LBT mode is operational and commonly used at several phased-array HFR installations, the implementation to commercial direction-finding systems does not appear to be available yet. In this paper, a proof-of-concept is provided for the implementation of the LBT mode for commercial SeaSonde HFRs deployed in Australia, with potential for applications in other networks and installations elsewhere. Potential critical aspects for systems operated under this configuration are also pointed out. Both the receiver and the transmitter antennas may lose efficiency if the frequency offset from the resonant frequency or calibration pattern are too large. Radial resolution clearly degrades when a dynamical adaptation of the bandwidth is performed, which results in non-homogeneous spatial resolution and reduction of the quality of the data. A recommendation would be to perform the LBT-adapt scans after a full measurement cycle (1-h or 3-h, depending on the system configuration) is concluded. Mutual cross-interference from clock offsets between two HFR systems may bias the frequency scans when the site computers controlling data acquisitions are not properly time-synchronized.

The Global High Frequency Radar Network - Hugh Roarty; Thomas Cook; Lisa Hazard; Doug George; Jack Harlan; Simone Cosoli; Lucy Wyatt; Enrique Alvarez Fanjul; Eric Terrill; Mark Otero; John Largier; Scott Glenn; et al. (Frontiers in Marine Science, 2019)

Sensitivity of HF radar-derived surface current self-organizing maps to various processing procedures and mesoscale wind forcing - Ivica Vilibić; Hrvoje Kalinić; Hrvoje Mihanović; Simone Cosoli; Martina Tudor; Nedjeljka žagar; Blaž Jesenko (Computational Geosciences, 2016)

A hidden Markov approach to the analysis of space–time environmental data with linear and circular components - Francesco Lagona; Marco Picone; Antonello Maruotti; Simone Cosoli (Stochastic Environmental Research and Risk Assessment, 2015)